SEMINAL CHARACTERISTICS AND THEIR INTERRELATIONSHIPS IN GIR BULLS - VALA,, S B; VALA, K B; SOLANKI, G B; PADODARA, R J; PARMAR, K H (The Indian Journal of Animal Reproduction, 2021)
The present investigation was undertaken on semen quality parameters and their interrelationshipson three Gir bulls (5 years old) maintained at Cattle Breeding Farm, Junagadh. Semen ejaculates (n=30,10/bull) were collected using artificial vagina (Danish model) once weekly and were soon evaluated forphysico-morphological attributes. The ejaculate volume, sperm concentration, mass motility (0-5 scale),individual sperm motility, sperm viability, sperm abnormality, HOST reactive spermatozoa, and acrosomeintegrity were found to be 7.93±1.72 ml, 1376.90±55.21 million/ml, 3.70±0.08, 83.67±0.93 %, 87.03±0.74%, 9.87±0.52 %, 90.17±0.47 % and 75.30 ±1.07 %, respectively. There was a significant (P
Keywords: Gir bull; HOS test; Pearson’s correlations; Semen quality; Variation between bulls